On SU(3) Effective Models and Chiral Phase Transition - Abdel Nasser Tawfik; Niseem Magdy (Advances in High Energy Physics)
Sensitivity of Polyakov Nambu-Jona-Lasinio (PNJL) model and Polyakov linear sigma-model (PLSM) has been utilized in studying QCD phase-diagram. From quasi-particle model (QPM) a gluonic sector is integrated into LSM. The hadron resonance gas (HRG) model is used in calculating the thermal and dense dependence of quark-antiquark condensate. We review these four models with respect to their descriptions for the chiral phase transition. We analyze the chiral order parameter, normalized net-strange condensate, and chiral phase-diagram and compare the results with recent lattice calculations. We find that PLSM chiral boundary is located in upper band of the lattice QCD calculations and agree well with the freeze-out results deduced from various high-energy experiments and thermal models. Also, we find that the chiral temperature calculated from HRG is larger than that from PLSM. This is also larger than the freeze-out temperatures calculated in lattice QCD and deduced from experiments and thermal models. The corresponding temperature and chemical potential are very similar to that of PLSM. Although the results from PNJL and QLSM keep the same behavior, their chiral temperature is higher than that of PLSM and HRG. This might be interpreted due the very heavy quark masses implemented in both models.